Pengaruh Literasi Keuangan, Perilaku Keuangan, dan Financial Technology terhadap Keputusan Investasi Mahasiswa - Permatasari, Noviana Putri; Waluyo, Dwi Eko; Subagyo, Herry; Prawitasari, Dian (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to examine the impact of financial literacy, financial behavior, and financial technology on investment decisions among students in Semarang. The methodology used is quantitative, utilizing a survey approach and data collection through a Likert scale questionnaire administered to active students who have used investment applications. The collected data was then analyzed using Structural Equation Modeling (SEM) techniques to evaluate the impact of each variable on investment decisions. The analysis results indicate that financial literacy, financial behavior, and financial technology have a significant and positive impact on students' investment decision-making. These findings contribute significantly to the advancement of financial literacy and the increased utilization of technology among students, aiming to enhance the quality of investment decision-making at the university level.